2014
DOI: 10.1063/1.4903767
|View full text |Cite
|
Sign up to set email alerts
|

Structures of two intermediate phases between the B1 and B2 phases of PbS under high pressure

Abstract: The structural transitions of PbS were investigated at pressures up to 50 GPa using synchrotron powder and single crystal X-ray diffraction (XRD) methods in diamond anvil cells. We found two intermediate phases between the B1 phase under atmospheric pressure and the B2 phase at 21.1 GPa, which is different to previous reports. The structures of these two intermediate phases were indexed as B27 and B33, respectively. Their structural parameters were investigated using density functional theory (DFT) calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…We note that this NaCl (B1) → TlI (B33) → CsCl (B2) phase transition is known to exist in TlI , and PbS ,, systems. The orthorhombic TlI type ( Cmcm ) can be considered to be a rather distorted NaCl structure type .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We note that this NaCl (B1) → TlI (B33) → CsCl (B2) phase transition is known to exist in TlI , and PbS ,, systems. The orthorhombic TlI type ( Cmcm ) can be considered to be a rather distorted NaCl structure type .…”
Section: Resultssupporting
confidence: 87%
“…The stacking order is ABAB . In the thallium iodide system, this orthorhombic modification of thallium iodide transforms to the CsCl type modification with increasing temperature, while in PbS, the same process occurs upon further increase in pressure. ,, In barium sulfide, we find a metastable TlI structure which might be observed at elevated pressures and temperatures (see Figure and Table ). Quenching or slow decompression of the high-pressure CsCl modification of BaS could be possible synthesis routes where TlI modification might be observed in the experiment.…”
Section: Resultsmentioning
confidence: 68%
“…PbS crystallizes in cubic structure (galena) at ambient pressure and undergoes phase transition to the orthorhombic structure at high pressures. However, the space group ( Cmca or Pnma ) of orthorhombic structure of PbS is under debate . Up to date, only one pressure‐dependent Raman study of PbS was reported; however, obtained Raman spectra were not conclusive about structure type …”
Section: Resultsmentioning
confidence: 99%
“…Generally, chalcogenide compounds undergo one or two phase transitions with increasing temperature or pressure. Of these, the transitions between NaCl-type (B1) and distorted-NaCl structures (cinnabar, Cmcm , Pnma , and R 3 m phases) play a significant role (Figure ), for example, transformations from cinnabar to B1, cinnabar to Cmcm , , B1 to Cmcm or Pnma , and Pnma to Cmcm , , are all observed under high pressure. In many cases, conclusions about these phase transitions and their nature are based on Bragg-diffraction studies.…”
Section: Introductionmentioning
confidence: 99%